2019
DOI: 10.1371/journal.pone.0220989
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus gattii alters immunostimulatory potential in response to the environment

Abstract: Cryptococcus gattii is a capsular fungal pathogen, which causes life-threatening cryptococcosis in immunocompetent individuals. This emerging pathogen is less likely to be recognized by innate immunity compared to traditional Cryptococcus neoformans strains. Previous studies indicate that C-type lectin receptors (CLRs), including dectin-1 and dectin-2, play a role in recognizing cryptococcal cells; however, it remains to be elucidated whether the receptors physically associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 52 publications
2
29
0
1
Order By: Relevance
“…Macrophage polarization occurs in different sources of macrophages and the microenvironment and innate immune receptors are major inductors in differentiation to M1 or M2 subsets ( Mantovani et al, 2004 ; Wang, Liang & Zen, 2014 ). The modulation of M1- and M2-type macrophage polarization can be orchestrated by C. gattii compounds through interactions with receptors on the cell surface ( Ueno et al, 2019 ). In this context, carbohydrates located in the C. gattii capsule can inhibit TLR2 and TLR4 signaling, which is a mechanism to subvert the host immune response.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophage polarization occurs in different sources of macrophages and the microenvironment and innate immune receptors are major inductors in differentiation to M1 or M2 subsets ( Mantovani et al, 2004 ; Wang, Liang & Zen, 2014 ). The modulation of M1- and M2-type macrophage polarization can be orchestrated by C. gattii compounds through interactions with receptors on the cell surface ( Ueno et al, 2019 ). In this context, carbohydrates located in the C. gattii capsule can inhibit TLR2 and TLR4 signaling, which is a mechanism to subvert the host immune response.…”
Section: Resultsmentioning
confidence: 99%
“…In brief, BM cells were cultivated in GM-CSF-containing medium for 6 days to induce BMDC deferentiation [15][16][17]. In some experiments, peritoneal exudate cells (PECs), including resident macrophages or the macrophage-like cell line J774A.1, were used instead of BMDCs.…”
Section: Preparation Of Bmdcs and Related Cellsmentioning
confidence: 99%
“…35,36) We demonstrated that capsular cryptococcal cells could not be recognized by immune cells without opsonization and that acapsular mutants are immediately engulfed by innate immune cells. 14,37,38) Cryptococcal cells can be opsonized with anti-GXM antibody, and opsonized capsular cells are phagocytized by innate immune cells. 39,40) Thus, it is reasonable to use GXM or GalXM as vaccine antigens to induce specific antibodies and AMI.…”
Section: Antigens and Carriersmentioning
confidence: 99%
“…69) It was shown that C. neoformans Cda2 recombinant protein prepared in Pichia pastoris was recognized by dectin-2 in B3Z reporter cells and DCs, and recombinant soluble dectin-2 physically bound to C. gattii cells. 38,70) Antigen-presenting cells (APCs) such as DCs can uptake MPs via PRRs and process MPs for antigen presentation to naive T cells. 71,72) Recombinant proteins generated in Escherichia coli (rCda1, rCda2, rCda3, rd25, and rSod1) are likely lacking glycosylation and similar to CPs are less recognizable as foreign antigens.…”
Section: Adjuvants and Actmentioning
confidence: 99%